Solve systems using elimination

Solve the system of equation by using elimination. Write your answer in Example (9,-7) NOT 9,-7parenthesis and use a comma.-4x + 5y = 52x - 5y = -15Solve the system of equation by using elimination. Write your answer in Example (9,-7) NOT 9,-7parenthesis and use a comma.2x + y = -43x - y = -11Solve the system of equation by using elimination. Write your answer in Example (9,-7) NOT 9,-7parenthesis and use a comma.-6x + 3y = -185x - 3y = 12Solve the system of equation by using elimination. Write your answer in Example (9,-7) NOT 9,-7parenthesis and use a comma.3x + 4y = 122x + 4y = 16Solve the system of equation by using elimination. Write your answer in Example (9,-7) NOT 9,-7parenthesis and use a comma.3x + 5y = -113x + y = -7Solve the system of equation by using elimination. Write your answer in Example (9,-7) NOT 9,-7parenthesis and use a comma.-4x + 6y = 0-4x + 2y = -8Solve the system of equation by using elimination. Write your answer in Example (9,-7) NOT 9,-7parenthesis and use a comma.2x - 3y = 142x + y = -10Solve the system of equation by using elimination. Write your answer in Example (9,-7) NOT 9,-7parenthesis and use a comma.x + y = -4-x + 2y = 13 |

Created with That Quiz —
where test making and test taking are made easy for math and other subject areas.